(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2018)
The importance of this research has been to rationalize the cost of producing maize seeds through the followers of modern techniques and methods in agricultural activities such as genetic engineering for increasing production efficiency of maize seeds as well as the importance of calculating seed cost rationalization through the ABC system and thus rationalizing government spending. The research is based on one hypothesis in two ways that the use of genetic engineering on maize seeds works to: one - increase production efficiency of seeds and savings in agricultural inputs. 2. Rationalize the costs of examining and planting maize seeds. In order to calculate the costs will be based on the cost system based on activities ABC. The research reached a number of conclusions, the most important: The application of genetic engineering on the seeds of maize productivity efficiency as well as its contribution to reduce the costs of testing and planting seeds, the needs of the market and the farmers of seed, which is a raw material involved in agriculture. The research led to a number of recommendations, including: Genetic engineering as a means to provide seeds in sufficient quantities to meet the needs of the market and farmers of seeds. The importance of this research has been to rationalization the cost of producing maize seeds through the followers of modern techniques and methods in agricultural activities such as genetic engineering for the purpose of increasing production efficiency of maize seeds as well as the importance of calculating seed cost rationalization through the ABC system and thus rationalizing government spending. The research is based on a single hypothesis that the use of genetic engineering on maize seeds works to increase production efficiency of seeds and savings in agricultural inputs, calculation of rationalization through the system of activity basis cost ABC The research reached a number of conclusions, the most important of which The application of genetic engineering to maize seeds achieves productivity efficiency to meet the needs of the market and farmers of seed, which is a raw material involved in agriculture. The research led to a number of recommendations, including: Genetic engineering as a means to provide seeds in sufficient quantities to meet the needs of the market and farmers of seeds.